Influence Of Restaurative Therapy On Marginal Periodontal Tissue - Arina Ciocan-Pendefunda; Norina Consuela Forna; Valeria Pendefunda (Romanian Society of Oral Rehabilitation, 2012)
The aim of this study is to evaluate the influence of fixed prosthodontics on the periodontal health status, emphasising the pathological changes induced by the restorative materials. Materials and methods The study group was made by 112 patients with 282 dental fixed bridges evaluated by clinical and paraclinical exams. The clinical evaluation included the age of the dental bridge, the material it was made of, the periodontal changes, the bleeding index. For the statistical processing of the data it was used STATISTICA, a special program for medical research. Results and discussions Periodontal changes consisted of significant values of periodontal bleeding index for 46.43% of the cases, periodontal pockets in 12.5% of the cases, recession in 3.57% of the studied cases. Conclusions There is a significant correlation between the material in use for the dental bridges and the presence of the periodontal damage, especially for the metal-acrylic and cast metal crowns.